Tác động của chính sách giám sát an toàn vĩ mô tới giá bất động sản tại Việt Nam - Pham Thi Hoang , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The paper aims at assessing the effectiveness of macroprudential policy as well as macroeconomic factors on housing price in Viet Nam during 2000–2018 period. Based on the OLS model, this paper found empirical evidence indicating that macroprudential policy instruments of State Bank such as imposing risk weight on loan for real estate business, and restrictions on entities who can borrow foreign currency loans were effective in reducing housing prices in Vietnam during 2000–2018 period. Macroeconomic factors such as hot credit growth and economic growth are important determinants of housing bubbles.